Islamic Humble Leadership in Sustaining Education Quality at Madrasa (Journal of Namibian Studies : History Politics Culture, 2023)
The leadership model in an educational institution plays a very important role in relation to school quality assurance. A leader holds the pinnacle of control in an organization and must be able to transform the vision and mission of the Institution so that it can be achieved optimally with effective and efficient work methods. Unfortunately, not all school principals have leadership characteristics that can serve their members rather than be served. This study aims to analyze humble leadership that can improve the quality of madrasah education. Humble leadership is the right choice for a leader to be able to optimize his leadership in the management practices of an increasingly complex and dynamic world of education. The methods used in data collection are observation, interviews, and documentation. Meanwhile, to ensure the validity of the data, researchers used source and technique triangulation. After the data is collected, the researcher analyzes it using the Cresswell model analysis. The findings of this study are that humble leadership can improve the process and quality of madrasah education management by maintaining good relations with its members, motivating them to continue developing, fostering a sense of belonging to the institution, motivating them to fight for common interests rather than personal interests and maintaining high moral standards.